PENINGKATAN DAYA INGAT MELALUI PEMBELAJARAN MEMBACA DAN MENULIS EFEKTIF TERPADU - , YULIATI (Pendidikan Dasar, 2008)
Abstract: This Studi was aimed to improve of mind of SDN Gadang I Malang  through the subject that they read by integrating of reading and writing effectively. The basis of the study is the process integrating  reading  and writing strategy with special reading and writing. (reading mind maping  and note taking). The research use colaboratively between teacher and research  were carried out in three  cycles was done with the following stage: planning, action observation, reflection, and revision of the planning for the next cycle. In the initial stage the reseacher observed the teaching learning activity for finding out the first fact. The result was reflection and using as a basis planned action  cycles 1,2 and so on, was orientation for improved the prosses and result study. The data were record with observation   (process activity checlist and self evaluating), interview, documentation, tape recorder and photo record. The data were then analyzed using circulair descriptive qualitative analyze by multyfunction principple. The result indicated that teaching integrating reading and writing effectively, have positive effect to improve reading and wrting ability, understanding of strategy , and the ascend of mind. The next apply should  support with the ascend understanding  of teacher for reading and writing study theories, the complet full of media.